THE IMPACT OF INTERNET LANGUAGE ON STYLISTIC CHARACTERISTICS OF MODERN LITERATURE (KONFERENSIYA, 2025)
The article examines how Internet language shapes the stylisticcharacteristics of contemporary literary discourse. It analyzes the emergence of newcommunicative norms within the digital environment, addressing both theconstructive and problematic aspects of these developments. Particular emphasis isplaced on the proliferation of slang and graphic abbreviations, as well as theirincreasing presence in fiction and journalistic writing